Listeria spp. and l. Monocytogenes isolated from food premises: Prevalence, characteristics, biofilm formation and antibacterial effect of detergents - Chen, Sook Ngoh (2024)
Listeria monocytogenes is a ubiquitous foodborne pathogen that can spread through food and food contact surfaces which lead to deadly listeriosis outbreaks, as was recently seen in United States and South Africa. Moreover, L. monocytogenes is widely found in food and food products in Malaysia by previous research study. As L. monocytogenes adheres to these surfaces and persist in food related environment with development of biofilm before reaching to a host to cause infection. This study aimed to determine the occurrence of L. monocytogenes, examine the antibiotic resistance profiles via classification of serotypes and virulent genes and compare L. monocytogenes from environment and lab cultured with biofilm study. A total of 322 samples were collected randomly from food industries in Perak from August 2018 to 2019. Prior to classification of serotype, virulence factor and antibiotic resistance research, L. monocytogenes was discovered and confirmed using a combination of plating and duplex polymerase chain reaction method. Then, the adherence, biofilm-forming ability, biofilm formation and elimination of environmental isolate were compared to ATCC 19112. Results revealed that 69 samples (21.42%) tested positive for Listeria and more than half of these samples (n=41/69, 59.42%) belonged to serogroup II.2 of L. monocytogenes and carried majority of evaluated virulent genes. About 98.48% isolates exhibited resistance against oxacillin followed by penicillin (50%) and clindamycin (45.45%). It was discovered that the type of strain, test surface, temperature and disinfection solutions were variables affecting the development and elimination of biofilm cells. Comparatively, ATCC strain of 19112 developed more biofilm cells than the environmental isolate, but it detached effectively with acid treatment. In conclusion, this study revealed that unhygienic food processing environments promote the growth of biofilm which subsequently contaminate food products and lead to listeriosis arise in Malaysia. Thus, continuous national surveillance programs, monitoring antibiotic resistance in treating L. monocytogenes and educating the food handlers with proper cleaning techniques are crucial for preventing the spread of multi-drug resistant L. monocytogenes.